PEMBUATAN 3D KARAKTER DESAIN MENGGUNAKAN TEKNIK LOD UNTUK OPTIMASI PADA GAME MOBILE - Arianto, Achmad Rizki; Kusnadi, Kusnadi; Parman, Suhadi (STMIK Sinar Nusantara, 2024)
Games are interactive simulations that entertain while enhancing problem-solving and comprehension skills. The rapid advancement in gaming technology has transitioned games from 2D to 3D, providing a more immersive visual experience. However, mobile games face significant challenges due to the limitations of processors, GPUs, and memory, which affect the performance of 3D models. This study case applies the Level of Detail (LOD) technique to address these issues. The LOD technique reduces the complexity of 3D models based on viewing distance, thus optimizing device resource usage. In creating 3D character designs, the author employs a design thinking methodology for user data collection. This research aims to develop and implement the LOD technique for 3D character modeling in mobile games, to improve game efficiency and performance while maintaining visual quality. The conclusion of this study shows that the application of Level of Detail techniques and good 3D modeling can help game developers to maintain optimal use of device resources.